Momfluencers sebagai Aktor Ekonomi Digital Lokal: Analisis Beauty Capital, Familial Trust, dan Business Stack di Kota Makassar - Muhrami, Siti Nardiyah; Hidayat, Rahmat; Muchtar, Yulnita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the role of momfluencers as local digital economic actors in Makassar, Indonesia, focusing on three main dimensions: beauty capital, familial trust, and business stack. Using a descriptive qualitative approach, ten momfluencers were purposively selected based on three criteria: having at least 10,000 active followers, consistent content production, and active collaboration with local SMEs. Data were collected through semi-structured interviews, social media content observation, and secondary data from official institutions. The findings indicate that beauty capital serves not only as an aesthetic strategy but also as a representation of modesty and Bugis-Makassar cultural identity. The familial trust dimension builds emotional closeness between momfluencers and their audiences through family narratives reflecting siri’ na pacce (the local values of honor, empathy, and social responsibility). Meanwhile, the business stack demonstrates a community-based digital monetization strategy that strengthens collaboration with local SMEs. Overall, the study concludes that momfluencers in Makassar function as socio-economic agents who integrate cultural values, digital ethics, and entrepreneurial innovation, representing empowered women driving inclusive growth within the regional creative economy ecosystem.